Genetic Diversity and Population Structure Analysis in Guar - Shubham Malani; Waltram Ravelombola; Aurora Manley; Hanh Pham (Plants)
Guar [Cyamopsis tetragonoloba (L.) Taub] was domesticated in India and Pakistan. It is mainly self-pollinated, bushy, and deeply tap-rooted. Guar seed endosperm contains galactomannan gum, which is used in many food products, pharmaceuticals, cosmetics, explosives, meat products, and pet foods, and in the textile industry, yet its genetic diversity remains largely underexplored. Using 7000 high-quality single nucleotide polymorphism (SNP) markers acquired from genotyping by sequencing (GBS), we analyzed the genetic diversity and population structure in 225 guar accessions from India, Pakistan, and the United States. Structure Harvester revealed that K = 3 had the best delta K, whereas K = 2 had the second-highest delta K. Three major genetic clusters (K = 3) were identified using population structure analysis, utilizing an admixture model: 156 accessions (69.3%) were classified into Q1, 23 accessions (10.2%) in Q2, and 16 accessions (7.1%) in Q3. The remaining 30 accessions (13.3%) were included in the admixture. In all three of the subpopulations at K = 3, most of the guar accessions came from India. We also found that these clusters mostly correlated with geographic origins. Results showed that the Q2 and Q3 subpopulations included only guar accessions from India. Genetic resources from Q2 and Q3 may represent an untapped reservoir for introducing beneficial variety into the U.S. breeding populations. This genetic diversity and population structure analysis of the guar gene pool will be of interest to conduct allele mining and donor parent selection for the development of new and better guar germplasm for desired traits.